Comparative Analysis of Codon Bias in the Chloroplast Genomes of Theaceae Species - Wang, Zhanjun; Cai, Qianwen; Wang, Yue; Li, Minhui; Wang, Chenchen; Wang, Zhaoxia; Jiao, Chunyan; Xu, Congcong; Wang, Hongyan; Zhang, Zhaoliang (Frontiers in Genetics, 2022)
Theaceae species are dicotyledonous angiosperms with extremely high ornamental and economic value. The chloroplast genome is traditionally used to study species evolution, expression of chloroplast genes and chloroplast transformation. Codon usage bias (CUB) analysis is beneficial for investigations of evolutionary relationships and can be used to improve gene expression efficiency in genetic transformation research. However, there are relatively few systematic studies of the CUB in the chloroplast genomes of Theaceae species. In this study, CUB and nucleotide compositions parameters were determined by the scripts written in the Perl language, CodonW 1.4.2, CU.Win2000, RStudio and SPSS 23.0. The chloroplast genome data of 40 Theaceae species were obtained to analyse the codon usage (CU) characteristics of the coding regions and the influence of the source of variation on CUB. To explore the relationship between the CUB and gene expression levels in these 40 Theaceae plastomes, the synonymous codon usage order (SCUO) and measure independent of length and composition (MILC) values were determined. Finally, phylogenetic analysis revealed the genetic evolutionary relationships among these Theaceae species. Our results showed that based on the chloroplast genomes of these 40 Theaceae species, the CUB was for codons containing A/T bases and those that ended with A/T bases. Moreover, there was great commonality in the CUB of the Theaceae species according to comparative analysis of relative synonymous codon usage (RSCU) and relative frequency of synonymous codon (RFSC): these species had 29 identical codons with bias (RSCU > 1), and there were 19 identical high-frequency codons. The CUB of Theaceae species is mainly affected by natural selection. The SCUO value of the 40 Theaceae species was 0.23 or 0.24, and the chloroplast gene expression level was moderate, according to MILC values. Additionally, we observed a positive correlation between the SCUO and MILC values, which indicated that CUB might affect gene expression. Furthermore, the phylogenetic analysis showed that the evolutionary relationships in these 40 Theaceae species were relatively conserved. A systematic study on the codon preference and expression of Theaceae species provides further evidence for their evolution and phylogeny.